Molecular identification and resistance phenotype analysis of Staphylococcus aureus from chicken sources - Gang Qiu; Yingying Liang; Meng Yang; Ying Chen; Tao Liu; Xiaoxiang Huo; Mengru An; Jiawang Kang; Ao Xue; Quanchao Ma; Yapei Rui (Journal of Applied Poultry Research)
Summary: The isolation, culture, PCR and biochemical test identification of 58 diseased materials collected from 6 different large-scale chicken farms in Xinyang City, 36 strains of Staphylococcus aureus were identified, and drug susceptibility tests were conducted to detect 16 kinds of drugs against Staphylococcus aureus from chickens. The antibacterial properties of these drugs inform clinical treatment decisions in this region. Test results indicated that on ordinary nutrient agar, medium-sized, smooth, convex, rounded, golden-yellow opaque colonies were observed. After Gram staining and microscopic examination, blue-purple, spherical, and non-transparent colonies were noted, resembling regularly arranged grape clusters. Following culture in nutrient broth, turbidity, sediment, and bacterial ring formation were observed. The biochemical tests aligned with the characteristics of Staphylococcus aureus, and the plasma coagulase test returned positive results. 58 samples of suspected S. aureus infection in four different scale chicken farms in Xinyang area of Henan Province were collected. Among them, 36 samples was confirmed by PCR detection to be Staphylococcus aureus. The bacterial isolation rate is 62%. Animal experiments have confirmed that the isolated strain is a wild strain with strong virulence. Chicken-derived Staphylococcus aureus exhibited high sensitivity to cefradine, cephalexin, ceftriaxone, erythromycin, clindamycin, ofloxacin, and enrofloxacin, moderate sensitivity to cefoperazone, doxycycline, amikacin, and ampicillin, and resistance to ampicillin, oxacillin, penicillin, tetracycline, gentamicin, and compound trimethoprim. The use of high-sensitivity antibiotics should be prioritized for treatment to mitigate the abuse of veterinary drugs and promote rational drug use.